Comparison of broiler performance using Plantain (Plantago lanceolata L.), Bio-Sel-E and commercial diet - Chacrabati, R; Chowdhury, R; Yesmin, S; Sano, H; Al-Mamun, M (Bangladesh Journal of Animal Science, 2013)
<!–[if gte mso 9]> <![endif]–><span style="font-size: 8.5pt; font-family: "Verdana","sans-serif"; mso-fareast-font-family: Calibri; mso-bidi-font-family: "Times New Roman"; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;">An experiment was conducted to determine the impact of Plantain (PL), Bio-Sel-E and commercial broiler diet on the growth performance, feed conversion ratio, performance index and carcass yield of broiler. A total of 160 day old broiler chicks (Cobb-500) were randomly distributed into four groups with four replication<span style="font-size: 8.5pt; font-family: "Verdana","sans-serif"; mso-fareast-font-family: Calibri; mso-bidi-font-family: "Times New Roman"; mso-ansi-language: EN-US; mso-fareast-language: JA; mso-bidi-language: AR-SA;"> in each group and<span style="font-size: 8.5pt; font-family: "Verdana","sans-serif"; mso-fareast-font-family: Calibri; mso-bidi-font-family: "Times New Roman"; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;"> having 10 birds in each<span style="font-size: 8.5pt; font-family: "Verdana","sans-serif"; mso-fareast-font-family: Calibri; mso-bidi-font-family: "Times New Roman"; mso-ansi-language: EN-US; mso-fareast-language: JA; mso-bidi-language: AR-SA;"> replication<span style="font-size: 8.5pt; font-family: "Verdana","sans-serif"; mso-fareast-font-family: Calibri; mso-bidi-font-family: "Times New Roman"; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;">. Basal diet was used for group 1 (control), Basal diet was supplemented with PL (0.5% of DM basis) and Bio-Sel-E (5g/50 birds in drinking water) for group 2 and 3 respectively and for group 4 used commercial broiler diet (Quality Feed Ltd.).<span style="font-size: 8.5pt; font-family: "Verdana","sans-serif"; mso-fareast-font-family: "MS Mincho"; mso-bidi-font-family: "Times New Roman"; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;"> <span style="font-size: 8.5pt; font-family: "Verdana","sans-serif"; mso-fareast-font-family: Calibri; mso-bidi-font-family: "Times New Roman"; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;">Total feed intake was similar <span style="font-size: 8.5pt; font-family: "Verdana","sans-serif"; mso-fareast-font-family: Calibri; mso-bidi-font-family: "Times New Roman"; mso-ansi-language: EN-US; mso-fareast-language: JA; mso-bidi-language: AR-SA;">among <span style="font-size: 8.5pt; font-family: "Verdana","sans-serif"; mso-fareast-font-family: Calibri; mso-bidi-font-family: "Times New Roman"; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;">the groups.<span style="font-size: 8.5pt; font-family: "Verdana","sans-serif"; mso-fareast-font-family: Calibri; mso-bidi-font-family: "Times New Roman"; mso-ansi-language: EN-US; mso-fareast-language: JA; mso-bidi-language: AR-SA;"> F<span style="font-size: 8.5pt; font-family: "Verdana","sans-serif"; mso-fareast-font-family: Calibri; mso-bidi-font-family: "Times New Roman"; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;">eed conversion ratios <span style="font-size: 8.5pt; font-family: "Verdana","sans-serif"; mso-fareast-font-family: Calibri; mso-bidi-font-family: "Times New Roman"; mso-ansi-language: EN-US; mso-fareast-language: JA; mso-bidi-language: AR-SA;">of <span style="font-size: 8.5pt; font-family: "Verdana","sans-serif"; mso-fareast-font-family: Calibri; mso-bidi-font-family: "Times New Roman"; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;">PL<span style="font-size: 8.5pt; font-family: "Verdana","sans-serif"; mso-fareast-font-family: Calibri; mso-bidi-font-family: "Times New Roman"; mso-ansi-language: EN-US; mso-fareast-language: JA; mso-bidi-language: AR-SA;"> diet, Bio-Sel-<span style="font-size: 8.5pt; font-family: "Verdana","sans-serif"; mso-fareast-font-family: Calibri; mso-bidi-font-family: "Times New Roman"; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;">E<span style="font-size: 8.5pt; font-family: "Verdana","sans-serif"; mso-fareast-font-family: Calibri; mso-bidi-font-family: "Times New Roman"; mso-ansi-language: EN-US; mso-fareast-language: JA; mso-bidi-language: AR-SA;"> diet,<span style="font-size: 8.5pt; font-family: "Verdana","sans-serif"; mso-fareast-font-family: Calibri; mso-bidi-font-family: "Times New Roman"; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;"> and commercial broiler <span style="font-size: 8.5pt; font-family: "Verdana","sans-serif"; mso-fareast-font-family: Calibri; mso-bidi-font-family: "Times New Roman"; mso-ansi-language: EN-US; mso-fareast-language: JA; mso-bidi-language: AR-SA;">diet<span style="font-size: 8.5pt; font-family: "Verdana","sans-serif"; mso-fareast-font-family: Calibri; mso-bidi-font-family: "Times New Roman"; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;"> were comparable, and were lower (P<0.05) than the control<span style="font-size: 8.5pt; font-family: "Verdana","sans-serif"; mso-fareast-font-family: Calibri; mso-bidi-font-family: "Times New Roman"; mso-ansi-language: EN-US; mso-fareast-language: JA; mso-bidi-language: AR-SA;"> diet.<span style="font-size: 8.5pt; font-family: "Verdana","sans-serif"; mso-fareast-font-family: Calibri; mso-bidi-font-family: "Times New Roman"; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;"> Significantly higher body weight gain and performance index were found in PL, Bio-Sel-E and commercial broiler diet groups than control diet. The dressing yield of PL diet and commercial broiler diet were comparable, and they were higher (P<0.05) than Control diet and Bio-Sel-E diet. It could be concluded that the Supplementation of 0.5% PL in the diet had positive effect on growth, feed intake, feed conversion ratio, performance index and carcass characteristics of broilers almost similar of Bio-Sel-E and commercial broiler diet. <!–[if gte mso 9]> Normal 0 false false false EN-US X-NONE X-NONE MicrosoftInternetExplorer4 <![endif]–> <!–[if gte mso 9]> <![endif]–><!–[if gte mso 10]> <![endif]–> DOI: http://dx.doi.org/10.3329/bjas.v42i2.18492 <span style="font-size: 12.0pt; line-height: 115%; font-family: "Times New Roman","serif"; mso-fareast-font-family: Calibri; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA; mso-bidi-font-weight: bold;">Bang. J. Anim. Sci. 2013. 42 (2): 123-130 <span style="font-size: 8.5pt; font-family: "Verdana","sans-serif"; mso-fareast-font-family: Calibri; mso-bidi-font-family: "Times New Roman"; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;"> <!–[if gte mso 9]> Normal 0 false false false EN-US X-NONE X-NONE <![endif]–><!–[if gte mso 9]> <![endif]–><!–[if gte mso 10]> <mce:style><! /* Style Definitions */ table.MsoNormalTable mso-style-name:"Table Normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-qformat:yes; mso-style-parent:""; mso-padding-alt:0in 5.4pt 0in 5.4pt; mso-para-margin-top:0in; mso-para-margin-right:0in; mso-para-margin-bottom:10.0pt; mso-para-margin-left:0in; line-height:115%; mso-pagination:widow-orphan; font-size:11.0pt; font-family:"Calibri","sans-serif"; mso-ascii-font-family:Calibri; mso-ascii-theme-font:minor-latin; mso-fareast-font-family:"Times New Roman"; mso-fareast-theme-font:minor-fareast; mso-hansi-font-family:Calibri; mso-hansi-theme-font:minor-latin; –> <!–[endif] –>